Esophageal perforation, inflammatory mediastinitis and pseudoaneurysm of the thoracic aorta as potential complications of botulinum toxin injection for achalasia. Issue 5 (1st December 2014) - Chao, Che yung; Raj, Ashok; Saad, Nivene; Hourigan, Luke; Holtmann, Gerald
<x xml:space="preserve">Abstract</x> Primary achalasia is a motility disorder of the esophagus involving impaired relaxation of the esophageal sphincter and, in later stages, dilatation and aperistalsis of the tubular esophagus. Endoscopic botulinum toxin injection to the lower esophageal sphincter is an effective and safe option in the treatment algorithm of achalasia, particularly in high‐surgical‐risk patients. In the present case report, we describe a rare complication of esophageal perforation following botulinum injection, resulting in associated inflammatory mediastinitis and formation of a pseudoaneurysm in the descending aorta. To the authors' knowledge, this is the first report in the literature of this rare complication of endoscopic botulinum injection. A contributing factor might have been the use of an injecting device with a significantly longer adjustable needle. Endoscopists should remain clinically vigilant to the potential complications associated with this common procedure.